2016
DOI: 10.1158/1535-7163.mct-15-0750
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Regulates EZH2 Transcription through Upregulation of C-MYC and Represents a Novel Therapeutic Target in Bladder Cancer

Abstract: People who develop bladder cancer frequently succumb to the intractable disease. Current treatment strategies are limited presumably due to the underlying molecular complexity and insufficient comprehension. Therefore, exploration of new therapeutic targets in bladder cancer remains necessary. Here, we identify that bromodomain-4 protein (BRD4), an important epigenome reader of bromodomain and extraterminal domain (BET) family member, is a key upstream regulator of enhancer of zeste homologue 2 (EZH2), and rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 43 publications
5
96
0
Order By: Relevance
“…Recent studies have identified BRD4 - EZH2 chromatin modification as an important growth pathway in bladder cancer, especially in tumors with loss of KDM6A , and shown in preclinical models that the BET inhibitor JQ1 and inhibition of EZH2 have therapeutic benefit (Ler et al, 2017; Wu et al, 2016). Recently, a Phase 2 study of Mocetinostat, a histone deacetylase inhibitor, in patients with locally advanced or metastatic urothelial carcinoma has completed accrual and results are awaited (NCT02236195).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified BRD4 - EZH2 chromatin modification as an important growth pathway in bladder cancer, especially in tumors with loss of KDM6A , and shown in preclinical models that the BET inhibitor JQ1 and inhibition of EZH2 have therapeutic benefit (Ler et al, 2017; Wu et al, 2016). Recently, a Phase 2 study of Mocetinostat, a histone deacetylase inhibitor, in patients with locally advanced or metastatic urothelial carcinoma has completed accrual and results are awaited (NCT02236195).…”
Section: Discussionmentioning
confidence: 99%
“…A-C, Tumour images and weights at experimental end-points in NC and shE2F4 NB4 xenografts (n = 5 for each group). 47 E2Fs have also been reported to manipulate EZH2 transcription in several malignancies including BC. E, Western blot analysis of cyclin D1, cyclin A2, P-Rb and CDK4 in tumour tissues of NC and shE2F4 groups.…”
Section: F I G U R Ementioning
confidence: 99%
“…A ChIP assay was performed using an EZ‐ChIP kit (Upstate Biotechnology, Lake Placid, NY, USA), as previously described 20. Briefly, chromatin DNA was immunoprecipitated with the corresponding antibody or normal IgG.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence from various cancer cell types that BRD4 can interact with the C‐MYC promoter and directly regulate its transcriptional expression 16, 17, 18. Furthermore, recent studies by one research group into the role of BRD4 in bladder cancer reported that BRD4 positively regulates enhancer of zeste homologue 2 ( EZH2 ) transcription through the upregulation of the C‐MYC promoter 19, 20…”
Section: Introductionmentioning
confidence: 99%